2014
DOI: 10.1163/22941932-00000058
|View full text |Cite
|
Sign up to set email alerts
|

Wood and Leaf Anatomy of Copaifera langsdorffii Dwarf Trees

Abstract: There are various parameters that affect tree height and may cause dwarfism. Our goal was to study the anatomical variations in the leaf and xylem structure in dwarf and normal trees of Copaifera langsdorffii and their correlation with physico-chemical properties of the soils. Trees from two spatially close but different vegetation types, transitional forest and rupestrian field, showed markedly different wood and leaf characteristics. Adult trees of C. langsdorffii show normal height (up to 25 m) in transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…When observing ray dimensions (multiplying the height by the width), we notice that RQ presents bulker rays than the trees growing in the other two soil types. For Copaifera langsdorffii in the previously noted study, Longui et al (2014) also found wider rays in trees in stony soils with low water retention and poorer nutrients. The authors suggested that higher ray volume in this context could confer greater potential for starch reserves, which may be important owing to the lower photosynthetic rate of C. langsdorffii plants with little soil water availability.…”
Section: Anatomical Featuressupporting
confidence: 67%
See 1 more Smart Citation
“…When observing ray dimensions (multiplying the height by the width), we notice that RQ presents bulker rays than the trees growing in the other two soil types. For Copaifera langsdorffii in the previously noted study, Longui et al (2014) also found wider rays in trees in stony soils with low water retention and poorer nutrients. The authors suggested that higher ray volume in this context could confer greater potential for starch reserves, which may be important owing to the lower photosynthetic rate of C. langsdorffii plants with little soil water availability.…”
Section: Anatomical Featuressupporting
confidence: 67%
“…In our study, larger vessels occurred in NV and narrower in LV. In a study with Copaifera langsdorffii with differences in vegetation type and soil attributes, Longui et al (2014) found narrower vessels in trees on stony soils with low water retention and poorer nutrients. Oliveira et al (2012) found vessels with larger diameters and frequency in latosol regions, compared with clayey soil in Eucalyptus grandis.…”
Section: Anatomical Featuresmentioning
confidence: 98%
“…The wood of Copaifera langsdorffii (Fabaceae-Caesalpinoideae) (Figure 2-7) is characterized by growth rings delimited by a clear series of oil-resin ducts and marginal parenchyma presenting high potential for dendrochronology, also observed by Marcati et al, (2001), Cury (2002), Tomazello Filho et al (2004, Marcati et al, (2006), Trevizor (2011), Sonsin et al, (2012 and Longui et al, (2014). The tree-ring formation, radial increment periodicity, phenology and ecological trends of wood anatomy were characterized by Alves and Angyalossy-Alfonso (2000), Lisi et al (2008) and Costa et al, (2015).…”
Section: Methodsmentioning
confidence: 88%